2016
DOI: 10.1080/15384101.2016.1208871
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of HTLV-1 Tax oncoprotein on the different estrogen-induced-ER α-mediated transcriptional activities

Abstract: The activated estrogen (E2) receptor α (ERα) is a potent transcription factor that is involved in the activation of various genes by 2 different pathways; a classical and non-classical. In classical pathway, ERα binds directly to E2-responsive elements (EREs) located in the appropriate genes promoters and stimulates their transcription. However, in non-classical pathway, the ERα can indirectly bind with promoters and enhance their activity. For instance, ERα activates BRCA1 expression by interacting with jun/f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 98 publications
0
9
0
Order By: Relevance
“…Known mechanisms of resistance to hormone therapies are complex and include epigenetic regulation of ESR1 expression [5,6], ESR1 mutations [712], alternative splicing events [3], ESR1 truncation and fusion events [13], post-translational modifications [14,15], alterations in the hormone binding domain [7,16], alter-native recruitment sites within the genome [17], differential recruitment of coregulators [18], feedback loops by ER target genes on expression/activity of ER [19 ● ], downstream actions of ER target genes on growth factor pathways and other signaling networks [20,21 ●● ], influences of the tumor microenvironment [22], and many others (Figure 1). The details of these mechanisms are beyond the scope of this review but have been thoroughly described by others [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Known mechanisms of resistance to hormone therapies are complex and include epigenetic regulation of ESR1 expression [5,6], ESR1 mutations [712], alternative splicing events [3], ESR1 truncation and fusion events [13], post-translational modifications [14,15], alterations in the hormone binding domain [7,16], alter-native recruitment sites within the genome [17], differential recruitment of coregulators [18], feedback loops by ER target genes on expression/activity of ER [19 ● ], downstream actions of ER target genes on growth factor pathways and other signaling networks [20,21 ●● ], influences of the tumor microenvironment [22], and many others (Figure 1). The details of these mechanisms are beyond the scope of this review but have been thoroughly described by others [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…HTLV-1 Tax onc-protein was found in our previous study to stimulate the transcriptional activity of ERa through the classical pathway (inducing the expression of genes controlled by ERE sequences) while it strongly inhibited BRCA1 expression through the non-classical pathway of ERa. 37,59 TPA which is known as a potent PKC activator and involved in the promotion of various kinds of tumors 51,52 was previously found to induce the expression of HTLV-1. 46,48,49,53 In the present study we examined the effect of TPA treatment on the expression of BRCA1 and genes controlled by ERE sequences in MCF-7 cells with or without Tax expression.…”
Section: Discussionmentioning
confidence: 99%
“…66 It was concluded that the inhibitory effects of TPA on the growth stimulation of MCF-7 cells by E2 was not due to a general inhibition of the expression of E2 responsive genes but probably due to a stimulation of TGF-b 1, acting as an autocrine inhibitory growth factor. 66 Based on our previous studies which showed that Tax strongly inhibited the E2-ERa induced activation of BRCA1 expression while stimulating E2-ERa induced activation of ERE dependent genes, 37,59 it was important to find out whether Tax has any effect on TPA activities on BRCA1 and ERE responsive genes. The results of this study showed that Tax has only minor inhibitory effect on TPA stimulation of BRCA1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ERα can act as a nuclear receptor and regulate target gene transcription via the “classical” model or the “nonclassical” model . In addition to its role in the “classical” model of gene regulation through oestrogen response elements (EREs) in promoter regions, ERα can form protein complexes with other transcription factors, such as Sp1, Ap1 and NF‐κB, to regulate gene transcription involved in the “nonclassical” model . These observations suggest that ERα can regulate a large variety of genes that are associated with the development of chemotherapy resistance in ER+ breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%